1979
DOI: 10.1007/bf01476510
|View full text |Cite
|
Sign up to set email alerts
|

Molekulargewichtsbezogene Analyse der physiologischen Proteinurie Neugeborener

Abstract: The physiological protien and glycoprotein excretions in the urine samples of a larger group of newborn infants were separated according to the molecular weights by SDS polyacrylamide gel electrophoresis and compared with the protein excretions of older children. We found higher proportions of albumin, of high molecular weight (MW = molecular weight greater than or equal to 150 000 dt) and of lower molecular weight (MW less than albumin 6800 dt) proteins in the first 24-h urine samples after birth. One week af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The results obtained by analysis of the molecular weights of urinary proteins in healthy newborns, separated by SDS-PAGE and stained with Coomassie Brilliant Blue G-250, reported by Thanner et al (23) confirmed the findings of previous mentioned authors for presence of glomerulo-tubular imbalance in early life. According to the number of separated protein fractions and their relative concentration (expressed as percent of total protein concentration) they concluded that proteinuria in healthy full-term neonates is predominantly tubular and is due to ineffective proximal tubular reabsorption of low molecular weight microproteins.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The results obtained by analysis of the molecular weights of urinary proteins in healthy newborns, separated by SDS-PAGE and stained with Coomassie Brilliant Blue G-250, reported by Thanner et al (23) confirmed the findings of previous mentioned authors for presence of glomerulo-tubular imbalance in early life. According to the number of separated protein fractions and their relative concentration (expressed as percent of total protein concentration) they concluded that proteinuria in healthy full-term neonates is predominantly tubular and is due to ineffective proximal tubular reabsorption of low molecular weight microproteins.…”
Section: Resultssupporting
confidence: 88%
“…There are also a great number of studies related to quantitative changes in some specific urinary proteins during the first month of life and later in early infancy and older children (19,20). There are only a few reports in literature regarding the SDS-PAGE electrophoretic profiles in healthy newborns (21)(22)(23).…”
Section: Resultsmentioning
confidence: 99%
“…Because a great number of proteinuric patients demonstrate not simply glomerular or tubular pattern, the ratio LMW/HMW or any other measure calculated on the basis of the relation between proteins of different size (e.g. glomerulo-tubular protein ratio, Thanner et al 1979) might appear to be normal even though there are distinct changes. Therefore it is important to determine LMW and HMW proteins quantitatively or at least semi-quantitatively in order not to lose information.…”
Section: Characterization Of Urinary Proteinsmentioning
confidence: 99%
“…Several LMW plasma proteins such as lysozyme (Pruzanski and Wilson 1977) or beta-2 microglobuiin (Hall and Vasiljevic 1973) which can easily be measured with a commercially available test kit, have been used as marker molecules. Another frequently applied method to characterize urinary proteins is the electrophoretic separation to demonstrate the molecular weight distribution (Boesken et al 1973;Balant et al 1974;Thanner et al 1979).…”
Section: Introductionmentioning
confidence: 99%